Pemberdayaan UMKM Melalui Pengembangan Bisnis Berbasis Ekonomi Syariah : (Pengabdian Kepada Masyarakat) - Andi Zakaria (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This community service program aims to empower Micro, Small, and Medium Enterprises (MSMEs) through business development based on the sharia economy. MSMEs have a strategic role in the economy, but still face various challenges, especially in the application of sharia economic principles that can increase competitiveness and the desire to do business. This program is designed to improve Islamic financial literacy, introduce business contracts in accordance with sharia, and provide halal digital marketing training. The method of implementing the activity includes a participatory approach with various stages, ranging from problem identification, training, mentoring, to success evaluation. The target of the program is MSME actors in certain regions who have great potential to adopt the concept of sharia economics in their businesses. The results of this activity showed an increase in participants' understanding of the concept of sharia economics, followed by changes in business practices that are more in line with Islamic principles. Some participants began to implement sharia contracts in their transactions, access sharia financing, and take advantage of halal branding-based digital marketing. This program also found several obstacles, such as low initial understanding of the sharia economy, limited access to Islamic financial institutions, and resistance to changes in the business system. However, through intensive strategy education and support from various parties, most of these challenges can be overcome. The conclusion of this activity is that business development based on the sharia economy can be a solution for MSMEs in increasing their competitiveness in the wider market. The next program recommendations include strengthening digital-based education, increasing access to sharia capital, and establishing a sharia-based MSME community as a forum for collaboration and sustainable business development.